ANTIOXIDANT EFFICACY AND CURCUMIN CONTENT OF TURMERIC (CURCUMA-LONGA L.) FLOWER - Kumar, Ajay; Singh, Monika; Singh, Prem Pratap; Singh, Sandeep Kumar; Raj, Pratima; Pandey, Kapil D. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The objective of the work is to evaluate the curcumin content, antioxidant activity and total phenol content of Curcuma longa flower. Methods: Curcumin content were analyzed through HPLC-PDA analysis. The antioxidant activity of the flower was determined by free radical scavenging activity of DPPH, and the total phenol content was determined using the Folin-Ciocalteu reagent through standard protocols. Results: The flowers had found about (3.87±0.5µg/g) of curcumin during HPLC-PDA analysis. The antioxidant activity (DPPH free radicals scavenging activity IC50) of the turmeric flower (3.2 µg/ml) was found near to the standard ascorbic acid (2.6 µg/ml). In addition to these, a significant amount of phenolics (210.45±1.32 mg GAE/100 g) was present in the turmeric flowers. Conclusion: The flowers of curcuma longa contains a significant amount of curcumin, antioxidant activity and phenol contents.